A complete reconstruction of the hyolithid skeleton. (January 2014) - Martí Mus, Mónica; Jeppsson, Lennart; Malinky, John M.
Abstract : Hyolithids are a group of Paleozoic lophotrochozoans with a four-pieced skeleton consisting of a conch, an operculum, and a pair of lateral 'spines' named helens. Both the conch and operculum are relatively well known and, to a certain extent, have modern analogues in other lophotrochozoan groups. The helens, on the other hand, are less well known and do not have clear modern analogues. This has hindered the knowledge of the complete morphology of the hyolithid skeleton, as well as other aspects of hyolithid biology, such as the organization of soft parts, and their ability to move. The material studied herein, consisting of disarticulated skeletal elements from the Silurian of Gotland, Sweden, illustrates a complete developmental sequence of a hyolithid species and includes the first complete, three-dimensionally preserved helens. Our material confirms that helens were massive skeletal elements, whose growth started proximally with the deposition of a central, coherent lamella. Further shell accretion took place around this lamella, but followed a particular accretion pattern probably constrained by the presence of marginal muscle attachment sites on the proximal-most portion of the helens. These muscle attachment sites were ideally located to allow a wide range of movements for the helens, suggesting that hyolithids may have been relatively mobile organisms.